With love, wherever you are : a novel - Mackall, Dandi Daley (Tyndale House Publishers, Inc., 2017)
"Everyone knows that war romances never last . . . After a whirlwind romance and wedding, Helen Eberhart Daley, an army nurse, and Lieutenant Frank Daley, M.D., are sent to the front lines of Europe with only letters to connect them for months at a time. Surrounded by danger and desperately wounded patients, they soon find that only the war seems real--and their marriage more and more like a distant dream. If they make it through the war, will their marriage survive? Based on the incredible true love story, With Love, Wherever You Are is an adult novel from beloved children's author Dandi Daley Mackall"--